The effectiveness of Max‐half‐Mchart over Max‐Mchart in simultaneously monitoring process mean and variability of individual observations. (2nd March 2021) - Kruba, Rumaisa; Mashuri, Muhammad; Prastyo, Dedy Dwi
Abstract: Control charts are widely used in industrial environments for the simultaneous or separate monitoring of the process mean and process variability. The Max‐Mchart is a multivariate Shewhart‐type simultaneous control chart that is used when monitoring subgroups. While this sampling design allows the computation of the generalized variance (GV) used to calculate the process variability, a GV chart cannot be plotted for individual observations. Hence, we cannot compute the single statistic in the Max‐Mchart. This study aims to overcome the aforementioned issue. To this end, first, we develop a new Max‐Mchart for individual observations by utilizing the statistic in the dispersion control chart. Second, instead of the standard normal distribution, we propose a new transformation using a half‐normal distribution to calculate the statistic for the process mean and process variability. Thus, the proposed chart is called the Max‐Half‐Mchart, whose control limit is calculated using the bootstrap approach. An evaluation based on the average run length values shows the robustness of the Max‐Half‐Mchart for the simultaneous monitoring of the process mean and process variability. The single statistic in the Max‐Half‐Mchart is more consistent with the statistic in Hotelling's T 2 and the dispersion chart than that of the Max‐Mchart.